Anecdotes to the life and times of Sir Richard Owen (1804–1892) in Lancaster. (November 2017) - Wessels, Q; Taylor, AM
Sir Richard Owen, a Lancastrian, was a prominent biologist, comparative anatomist, geologist, palaeontologist and known for coining the term dinosaur. His expertise in anatomical dissection proved to be one of his biggest assets and aided his career progression at the Royal College of Surgeons and the Zoological Society. Owen's apprenticeship in Lancaster helped him to gain expertise in anatomy and anatomical dissection. The authors aim to provide some novel contextual background to his childhood in Lancaster, his affection for his hometown and his contribution to Lancaster's sanitary reform. The latter aspect of his scientific accomplishments is typically overlooked.